Region Extraction in Mesh Intersection. (March 2023) - Antolin, Pablo; Buffa, Annalisa; Cirillo, Emiliano
Abstract: Region extraction is a very common task in both Computer Science and Engineering with several applications in object recognition and motion analysis, among others. Most of the literature focuses on regions delimited by straight lines, often in the special case of intersection detection among two unstructured meshes. While classical region extraction algorithms for line drawings and mesh intersection algorithms have proved to be able to deal with many applications, the advances in Isogeometric Analysis require a generalization of such problem to the case in which the regions to be extracted are bounded by an arbitrary number of curved segments. In this work we present a novel region extraction algorithm that allows a precise numerical integration of functions defined in different spline spaces. The presented algorithm has several interesting applications in contact problems, mortar methods, and quasi-interpolation problems. Highlights: An algorithm for mesh intersection in Volumetric B-spline models. An algorithm for the extraction of regions bounded by curvilinear segments. An algorithm for precise numerical integration of functions over interfaces. Possible applications in mortar methods and contact problems. Applications in volumetric filleting and multi-patch volumetric models.